Genetic risk of knee osteoarthritis: a sibling study. Issue 9 (12th August 2004) - Neame, R L; Muir, K; Doherty, S; Doherty, M
Abstract : Objectives: To determine whether there is a genetic contribution to knee osteoarthritis (OA) as defined by structural change on plain radiographs. Design: Sibling study. Comparison of knee OA prevalence in the community with knee OA prevalence among siblings of index cases with knee OA. Subjects: 490 knee OA index cases listed for total knee replacement and 737 of their siblings aged >40 years, 1729 community subjects aged >40 years. Main outcome measure: Odds ratio for radiographic knee OA in siblings v community participants. Results: The age, sex, and knee pain adjusted odds ratios in siblings were 2.9 (95% confidence interval 2.3 to 3.7) for tibiofemoral OA and 1.7 (1.4 to 2.2) for patellofemoral OA. This difference remained after adjustment for important environmental risk factors. The heritability estimate for knee OA was 0.62. Conclusions: Siblings are at increased risk of knee OA in comparison with the general population. This is likely to be due to genetic factors.